U.S. crude oil exports : restrictions and considerations - Pope, Michael (Editor of U.S. crude oil exports) (Energy policies, politics and prices series., 2014)
As a result of advanced oil drilling and extraction technologies (primarily horizontal drilling and hydraulic fracturing), crude oil production in the United States is growing and, according to Energy Information Administration (EIA) reference case projections, may reach 9.6 million barrels per day by 2019. Production of light tight oil (LTO) is, and is expected to be, the primary contributor to U.S. crude oil production growth in the near to medium term. This book provides background and context about the crude oil legal and regulatory framework, discusses motivations that underlie the desire.